2020
DOI: 10.1158/0008-5472.can-20-0789
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Obesity-Induced Macrophages during Preneoplastic Growth Promotes Mammary Epithelial Stem/Progenitor Activity, DNA Damage, and Tumor Formation

Abstract: ◥Obesity enhances breast cancer risk in postmenopausal women and premenopausal women with genetic or familial risk factors. We have shown previously that within breast tissue, obesity increases macrophage-driven inflammation and promotes expansion of luminal epithelial cell populations that are hypothesized to be the cells of origin for the most common subtypes of breast cancer. However, it is not clear how these changes within the microenvironment of the breast alter cancer risk and tumor growth. Using a high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…Mammary glands from HFD‐fed mice had significantly increased CD45 + CD11b + total myeloid cells compared to mammary glands from LFD‐fed mice ( p = .04, Figure 1D), confirming an increase in myeloid lineage cells that contribute to the chronic inflammatory microenvironment in the obese mammary gland. We have previously observed significantly elevated numbers of F4/80 + macrophages directly surrounding mammary ducts of HFD‐fed mice, 51 indicating that the increased numbers of macrophages are not confined to the CLS of the mammary gland.…”
Section: Resultsmentioning
confidence: 89%
“…Mammary glands from HFD‐fed mice had significantly increased CD45 + CD11b + total myeloid cells compared to mammary glands from LFD‐fed mice ( p = .04, Figure 1D), confirming an increase in myeloid lineage cells that contribute to the chronic inflammatory microenvironment in the obese mammary gland. We have previously observed significantly elevated numbers of F4/80 + macrophages directly surrounding mammary ducts of HFD‐fed mice, 51 indicating that the increased numbers of macrophages are not confined to the CLS of the mammary gland.…”
Section: Resultsmentioning
confidence: 89%
“…Taken together, the above findings suggest beneficial effect(s) of approaches aimed at manipulating Mϕ in BC, especially when taken together with previous reports attesting to Mϕ being an attractive target in mammary tumorigenesis, in general, and obesity-accelerated BC progression, in particular [ 16 , 30 , 33 , 34 , 94 ]. Yet, initial clinical studies (utilizing various agents decreasing Mϕ content) demonstrated mixed results [ 95 , 96 ]. The likely explanation for the somewhat limited benefit of the direct Mϕ targeting approach is provided by the dynamic nature and highly heterogeneous phenotypes of Mϕ [ 92 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of macrophages in obesity-associated cancer growth is however, complex. In a pre-neoplastic model, the depletion of macrophages in diet-induced obese mice led to greater numbers of mammary epithelial cells exhibiting DNA damage and increased mammary epithelial cell progenitor activity, suggesting that macrophages potentially play a modulatory role in the early stages of cancer development ( 287 ).…”
Section: Mechanisms Underlying the Obesity–cancer Relationship: Obesimentioning
confidence: 99%